Laser additive nano-manufacturing under ambient conditions. Issue 35 (28th August 2019) - Zhao, Chenglong; Shah, Piyush J.; Bissell, Luke J.
Abstract : A review of state-of-the-art additive nano-manufacturing with lasers under ambient conditions. Abstract : Additive manufacturing at the macroscale has become a hot topic of research in recent years. It has been used by engineers for rapid prototyping and low-volume production. The development of such technologies at the nanoscale, or additive nanomanufacturing, will provide a future path for new nanotechnology applications. In this review article, we introduce several available toolboxes that can be potentially used for additive nanomanufacturing. We especially focus on laser-based additive nanomanufacturing under ambient conditions.